Meningkatkan Keterampilan Motorik Halus Anak Usia Dini Melalui Kegiatan Melipat, Menempel dan Mewarnai di TK Aba 25 Medan - Fitria Harahap (Lembaga Pengembangan Kinerja Dosen, 2024)
This Professional Ability Development Program (PKP) aims to improve the fine motor skills of early childhood through folding, sticking, and coloring activities at TK 'Aisyiyah Bustanul Athfal 25 Medan. Fine motor skills, such as cutting, sticking, and coloring, are very important for the development of eye-hand coordination and prepare children for their academic and daily skills. This study used a descriptive method with a classroom action-based approach, where activities were carried out for three weeks from July 15 to July 29, 2024. The study participants consisted of 40 children divided into age groups of 4-6 years. The results of the study showed a significant increase in children's fine motor skills after participating in this program. Most children were able to show improvements in terms of accuracy and neatness in using tools such as scissors, glue, and colored pencils. In addition, children's enthusiasm and involvement in activities also increased. However, some children need more intensive guidance in developing their fine motor skills. Learning that integrates games and creative activities has been shown to be effective in helping children develop their fine motor skills. In conclusion, the implementation of PKP not only has a positive impact on improving children's fine motor skills, but also provides a fun and interesting learning experience for them. Thus, this program can be used as a model in developing basic skills for early childhood in other preschool educational institutions.